2015
DOI: 10.1177/1074840715576794
|View full text |Cite
|
Sign up to set email alerts
|

Families Living With Chronic Illness

Abstract: Beliefs can be described as the lenses through which we view the world. With emerging illness, beliefs about the illness experience become important for nurses to understand to enhance well-being and healing. The aim of this study was to illuminate illness beliefs of families living with chronic illness. A qualitative design was chosen, including repeated narrative research interviews with seven Swedish families living with chronic illness. Hermeneutic analysis was used to interpret the transcribed family inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 41 publications
(68 reference statements)
4
42
0
Order By: Relevance
“…In these circumstances the patient may adopt the ‘sick role’, relying on their family for support both with their illness and previous responsibilities [ 9 ]. It has been reported [ 10 ] that in patients with greater levels of family support, confidence between members is increased, and family ties strengthened, in times of need such as ill-health. Therefore, congruent beliefs about the illness are important in order to achieve successful family functioning and to enhance patient well-being [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these circumstances the patient may adopt the ‘sick role’, relying on their family for support both with their illness and previous responsibilities [ 9 ]. It has been reported [ 10 ] that in patients with greater levels of family support, confidence between members is increased, and family ties strengthened, in times of need such as ill-health. Therefore, congruent beliefs about the illness are important in order to achieve successful family functioning and to enhance patient well-being [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore recommend including homework, individual home sessions and booster sessions in future research to identify significant differences in long-term measurements in patients with PD and their informal caregivers. In clinical practice, it is necessary that health care professionals reinforce the knowledge of patients with PD and their caregivers about the illness over the time, because this knowledge can promote better self-management (Stenberg et al, 2016) and reduce uncertainty (Årestedt et al, 2015;Hurt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these non-illness-related factors also gain importance for family carers and Navarta-Sánchez et al (2016) concluded that both people with PD and carers' quality of life is clearly influenced by the psychosocial adjustment to illness, which significantly depends on coping skills, regardless the disabling and degenerative nature of PD (Navarta-Sanchez et al, 2017). Consequently, assessments and interventions should not only focus on the patient but also on the family, since it has been established that their experience of the adaptation process is comparable and that similar factors could influence this adjustment (Årestedt, Benzein, & Persson, 2015;Årestedt, Benzein, Persson, & Rämgård, 2016;Årestedt, Persson, & Benzein, 2014;Golics, Basra, Salek, & Finlay, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%